Crowd-induced lateral bridge vibration - Carroll, Seàn P. (2013)
Vibration induced by walking pedestrians has motivated research in the civil engineering community for many years. An area within this broad field that has received particular attention is the dynamic interaction that can occur between pedestrians and laterally flexible bridge structures. Perhaps the most notable example occurring on the opening day of London's Millennium Bridge. The enduring interest in this research problem is fuelled by two of its key features; (i) the sensitivity and adaptability of human balance to lateral motion and (ii) the spatial and temporal variation in flow characteristics exhibited by a pedestrian crowd. Both of these features are addressed herein.